Review of Kelly Askew. 2002. Performing the Nation: Swahili Music and Cultural Politics in Tanzania. Chicago and London: University of Chicago Press - Eisenberg, Andrew (Current Musicology, 2003)
If the last few decades of postcolonial critique have accomplished anything, it has been to cast a bright light on certain elephants that have too long resided, invisible, in cultural anthropology’s living room. The largest of these has been, of course, the nation-state. It took years of searching cri-tiques, but citizenship, nationalism, and state fetishism have finally become stock anthropological topics. The evidence of this shift may not yet be fully felt in the academic publishing world; however, if the list of dissertation topics in North America’s top anthropology departments is any indication, an "anthropology of the state" is no longer an arcane idea.